Driving fiber to the home. - Kettler, D. (IEEE Communications magazine)
BellSouth is currently operating the first ATM passive optical network fiber to the home system in North America. This article describes the architecture, service set, field experiences, next steps, relationships with data-centric core networks, potential FTTH deployment scenarios, and the opportunities and challenges associated with FTTH.